SOSIALISASI DAN PARTISIPASI DALAM OLAHRAGA - Erlich Ginting; Siregar, Ihsan; Sabar Hutabarat; Rahel Mutia; Tessa Silalahi; Yan Indra Siregar; Putra Arima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sports socialization is the process by which individuals learn the values, norms, attitudes, and behaviors related to sport through social interaction. Meanwhile, sports participation is the involvement of individuals or groups in various sporting activities, whether as participants, spectators, or organizers of sporting activities. The purpose of this article is to analyze the relationship between socialization and sport participation and the factors that influence both. The method used is a literature review, examining various scientific sources related to the sociology of sport. The results of the study indicate that family, school, peers, mass media, and the social environment play a significant role in shaping an individual's interest in and participation in sport. The more effective the sport socialization process, the higher the level of community participation in sporting activities. Therefore, synergy between various parties is needed to improve the culture of sport in society.